2022
DOI: 10.3390/cancers14051185
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Pan-Cancer Classification Model Reveals Tissue-of-Origin Specific Gene Expression Signatures

Abstract: Cancer tissue-of-origin specific biomarkers are needed for effective diagnosis, monitoring, and treatment of cancers. In this study, we analyzed transcriptomics data from 37 cancer types provided by The Cancer Genome Atlas (TCGA) to identify cancer tissue-of-origin specific gene expression signatures. We developed a deep neural network model to classify cancers based on gene expression data. The model achieved a predictive accuracy of >97% across cancer types indicating the presence of distinct cancer tissu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…In fact, accumulating evidence has demonstrated the inevitable association between ER stress and the development of multiple cancers, including KIRC (Chen and Cubillos-Ruiz, 2021;Varone et al, 2021). Recently, according to numerous research studies, multiple gene models, which are applied to predict outcomes and therapeutic effect, seem to have high credibility (Divate et al, 2022;Zhai et al, 2022). However, most of the research studies focus on the effect of ER stress in cancer progression and metastasis, and few studies have illustrated the prognostic value of ER stress-related genes in cancers, especially in KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, accumulating evidence has demonstrated the inevitable association between ER stress and the development of multiple cancers, including KIRC (Chen and Cubillos-Ruiz, 2021;Varone et al, 2021). Recently, according to numerous research studies, multiple gene models, which are applied to predict outcomes and therapeutic effect, seem to have high credibility (Divate et al, 2022;Zhai et al, 2022). However, most of the research studies focus on the effect of ER stress in cancer progression and metastasis, and few studies have illustrated the prognostic value of ER stress-related genes in cancers, especially in KIRC.…”
Section: Discussionmentioning
confidence: 99%
“…Schaefera et al explore why some genetic alterations are only relevant in specific types of cancer, concluding that the tissue microenvironment is a determining factor in this process (44). Two other studies have demonstrated that expression signatures can help classify the tissue for cancers of unknown primary origin, which presents a possible application of using the transcriptome signatures with tissue specificity in oncology (45, 46). Our work, besides adding novel knowledge to this field, corroborates studies such as that from Hu et al, which showed that in cancer, there is a decrease in the expression of some tissue-specific genes, and Pei et al, which showed that it is common for cancers to acquire specific expression profiles from other organs (47, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Cancers could be categorized as per the main point of action, such as breast, lung, prostate, liver, kidney, and brain (Divate et al, 2022 ).…”
Section: Human Cancer Categorizationsmentioning
confidence: 99%